IGF1R is a mediator of sex-specific metabolism in mice: Effects of age and high-fat diet - Pérez-Matute, Patricia; López, Icíar P.; Íñiguez, María; Recio-Fernández, Emma; Torrens, Raquel; Piñeiro-Hermida, Sergio; Alfaro-Arnedo, Elvira; Chau, Luong; Walz, Christina; Hoeflich, Andreas; Oteo, José A.; Pichel, José G. (Frontiers in Endocrinology, 2022)
Objective: We aimed to investigate the short and long-term metabolic consequences of IGF1R systemic gene deficiency in mice. Methods: UBC-CreERT2, Igf1rfl/fl mutant mice were used to suppress IGF1R signaling in adult tissues by inducing postnatal generalized Igf1r deletion with tamoxifen. Animals were analyzed at two different ages: i) 13-weeks old young mice, and ii) 12-months old middle-aged mice. In addition, the effects of 10 weeks-long high-fat diet (HFD) were investigated in middle-aged mice. Results: Young IGF1R-deficient mice were insulin-resistant, with high IGF1, growth hormone (GH) and IGFBP3, as well as low IGFBP2 circulating levels. Males also presented increased triglycerides in liver. In contrast, middle-aged mice did not clearly show all of these alterations, suggesting possible compensatory effects. Middle-aged IGF1R-deficient male mice were able to counteract the negative effects induced by aging and HFD in adiposity, inflammation and glucose metabolism. A metabolic sexual dimorphism dependent on IGF1R was observed, especially in middle-aged mice. Conclusions: These results demonstrate that IGF1R is involved in metabolic homeostasis, with effects modulated by diet-induced obesity and aging in a sex dependent manner. Thus, IGF1R deficiency in mice is proposed as a useful tool to understand metabolic alterations observed in patients with IGF1R gene deletions.